Preventing post-stroke dementia. The MARCH Trial. Protocol and statistical analysis plan of a randomized clinical trial testing the safety and efficacy of Maraviroc in post-stroke cognitive impairment. (September 2022) - Assayag, Einor Ben; Molad, Jeremy; Seyman, Estelle; Rotschild, Ofer; Zeltzer, Ehud; Sadeh-Gonik, Udi; Bregman, Noa; Alpernas, Aviva; Segal, Yahel; Bashat, Dafna Ben; Nathan, Talya; Hawwari, Muhamad; et al.
Background: Current evidence suggest that 25%–33% of stroke-survivors develop post-stroke cognitive impairment (PSCI). The licensed drug Maraviroc, a CCR5-antagonist, is postulated to act via a neuroprotective mechanism that may offer the potential of preventing progression to vascular dementia. Our hypothesis: Maraviroc may have the potential to augment learning skills and cognitive performance by affecting synaptic plasticity, along with neuro-inflammatory modulation in patients with cerebral small vessel disease (SVD) and PSCI. Design: MARCH is a multi-center, double-blind randomized-control Phase-II trial of Maraviroc 150 or 600 mg/day versus placebo for 12-months in five stroke centers in Israel. Included are patients diagnosed with recent (1–24 months) subcortical stroke who experience mild PSCI and have evidence of white matter lesions and SVD on neuroimaging. Outcomes: Primary outcomes: 1. Change in cognitive scores. 2. Drug related adverse events. Secondary outcomes: change in functional and affective scores, MRI-derived measures, inflammatory markers, carotid atherosclerosis, cerebrospinal-fluid biomarkers in a sub-study. A sample size of 60 in each treatment group and 30 in the placebo group (total – 150 participants) provides 80% power between the treatment and the placebo groups. Conclusions: The results of this work could lead to a novel, readily available, therapeutic avenue to reduce PSCI, and possibly other pathologies. This study will test safety and effectiveness of Maraviroc in limiting cognitive deterioration and/or post stroke cognitive impairment in patients with cerebral small vessel disease. Schedule: First-patient first-visit was May 2021. Recruitment to complete in 2023, follow-up to complete in 2024.